Supporting shared decision-making for older people with multiple health and social care needs: a protocol for a realist synthesis to inform integrated care models. Issue 2 (7th February 2017) - Bunn, Frances; Goodman, Claire; Manthorpe, Jill; Durand, Marie-Anne; Hodkinson, Isabel; Rait, Greta; Millac, Paul; Davies, Sue L; Russell, Bridget; Wilson, Patricia
Abstract : Introduction: Including the patient or user perspective is a central organising principle of integrated care. Moreover, there is increasing recognition of the importance of strengthening relationships among patients, carers and practitioners, particularly for individuals receiving substantial health and care support, such as those with long-term or multiple conditions. The overall aims of this synthesis are to provide a context-relevant understanding of how models to facilitate shared decision-making (SDM) might work for older people with multiple health and care needs, and how they might be applied to integrated care models. Methods and analysis: The synthesis draws on the principles of realist inquiry, to explain how, in what contexts and for whom, interventions that aim to strengthen SDM among older patients, carers and practitioners are effective. We will use an iterative, stakeholder-driven, three-phase approach. Phase 1: development of programme theory/theories that will be tested through a first scoping of the literature and consultation with key stakeholder groups; phase 2: systematic searches of the evidence to test and develop the theories identified in phase 1; phase 3: validation of programme theory/theories with a purposive sample of participants from phase 1. The synthesis will draw on prevailing theories such as candidacy, self-efficacy, personalisation and coproduction. Ethics and dissemination: Ethics approval for the stakeholder interviews was obtained from the University of Hertfordshire ECDA (Ethics Committee with Delegated Authority), reference number HSK/SF/UH/02387. The propositions arising from this review will be used to develop recommendations about how to tailor SDM interventions to older people with complex health and social care needs in an integrated care setting.